Deadlock prevention by acyclic orientations - Bermond, Jean-Claude; Ianni, Miriam Di; Flammini, Michele; Pérennès, Stéphane (Discrete Applied Mathematics, 2003)
Deadlock prevention for routing messages has a central role in communication networks, since it directly influences the correctness of parallel and distributed systems. In this paper, we extend some of the computational results presented in Second Colloquium on Structural Information and Communication Complexity (SIROCCO), Carleton University Press, 1995, pp. 1–12 on acyclic orientations for the determination of optimal deadlock-free routing schemes. In this context, minimizing the number of buffers needed to prevent deadlocks for a set of communication requests is related to finding an acyclic orientation of the network which minimizes the maximum number of changes of orientations on the dipaths realizing the communication requests. The corresponding value is called the rank of the set of dipaths. We first show that the problem of minimizing the rank is NP-hard if all shortest paths between the couples of nodes wishing to communicate have to be represented and even not approximable if only one shortest path between each couple has to be represented. This last result holds even if we allow an error which is any sublinear function in the number of couples to be connected. We then improve some of the known lower and upper bounds on the rank of all possible shortest dipaths between any couple of vertices for particular topologies, such as grids and hypercubes, and we find tight results for tori.